The Exploitation of Root-sourced Signals to Reduce Irrigation and to Regulate Leaf Growth of Pepper Plants Capsicum annuum L. - Awad, Mohamed Hamad; Ismail, Mohd Razi; Mahmood, Maziah; Tengku Muda Mohamed, Mahmud (Universiti Putra Malaysia Press, 2002)
The effect of partial root drying (PRD) on growth and physiological responses of pepper plants Capsicum annuum L. cultivar MC12 was investigated under high temperatures and a humid tropical climate. The leaf water potential, photosynthetic rate, stomatal conductance and transpiration rate of Capsicum plants grown under PRD over a period of 10 days were lower than those grown under well watered conditions. Removal of the droughted roots resulted in resumption of all leaf gas exchange parameters confirming the presence of signals coming directly from the droughted roots. Leaf growth rate was negatively affected by PRD techniques; as a consequence leaf area per plant was reduced. Total fruit yield ofPRD plants was about 73% of the control plants' fruit yield while the amount of water added to the PRD plants was half the quantity added to the controls.